2022
DOI: 10.1155/2022/3347166
|View full text |Cite|
|
Sign up to set email alerts
|

Prevention and Detection Research of Intelligent Sports Rehabilitation under the Background of Artificial Intelligence

Abstract: Artificial intelligence can bring convenience to human life. In the field of sports rehabilitation, the application of artificial intelligence is becoming more and more in-depth. This paper is aimed at studying the prevention and detection of sports rehabilitation in the context of artificial intelligence and proposing a compliance control method for lower limb rehabilitation robots based on artificial neural networks. In this paper, a double closed-loop control system is designed: the outer loop is an adaptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Applied Bionics and Biomechanics has retracted the article titled “Prevention and Detection Research of Intelligent Sports Rehabilitation under the Background of Artificial Intelligence” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Applied Bionics and Biomechanics has retracted the article titled “Prevention and Detection Research of Intelligent Sports Rehabilitation under the Background of Artificial Intelligence” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%
“…Applied Bionics and Biomechanics has retracted the article titled "Prevention and Detection Research of Intelligent Sports Rehabilitation under the Background of Artificial Intelligence" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], significant concerns were identified with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%